Ритм: [стихотворения] / Иван Бунин ; [иллюстрации Н. Устинова] - Бунин Иван Алексеевич (Серия "Великие поэты", 2011)
Экземпляры: Д. О. (20190619) / Инвентарный номер: 46741 / Цена: 180.00 / Сис.шифр: Р1 / Авт.знак: Б 91 / ГРНТИ: 17.82 / ББК: 84 (2Рос=Рус)1